The relationship between post-traumatic stress symptoms severity, coping style, perceived social support, extent of service experience, age, and gender within the Western Cape police service - Jones, Russell (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA) -- University of Stellenbosch, 2004.